International voluntary-based land consolidation approaches and their adaptability to experimental farm-based land consolidation in Finland - Sulonen, Kimmo (Nordic Journal of Surveying and Real Estate Research, 2018)
There is an ongoing need for different approaches to land consolidation in Finland, especially ones based on voluntary and flexible principles. One such approach is farm-based land consolidation, which for the time being is operating on an experimental state. To test the possibilities of the experimental land consolidation, international approaches should be investigated and evaluated. This research aims to find and compare suitable international voluntary based land consolidations and their aspects and how these aspects are adaptable into the Finnish system. The adaptability is evaluated in the viewpoint of the experimental farm based land consolidation approach focused on voluntary and flexible principles. The experimental approach is based on a traditional comprehensive land consolidation model. The research is conducted using method of qualitative direct content analysis for the data acquired in secondary and primary researches and themed interview for acquiring the empirical data. In practice, the data was obtained by studying existing studies and documents and interviewing the key land consolidation specialists involved.